1999
DOI: 10.1084/jem.189.8.1181
|View full text |Cite
|
Sign up to set email alerts
|

SHP2-interacting Transmembrane Adaptor Protein (SIT), A Novel Disulfide-linked Dimer Regulating Human T Cell Activation

Abstract: T lymphocytes express several low molecular weight transmembrane adaptor proteins that recruit src homology (SH)2 domain–containing intracellular molecules to the cell membrane via tyrosine-based signaling motifs. We describe here a novel molecule of this group termed SIT (SHP2 interacting transmembrane adaptor protein). SIT is a disulfide-linked homodimeric glycoprotein that is expressed in lymphocytes. After tyrosine phosphorylation by src and possibly syk protein tyrosine kinases SIT recruits the SH2 domain… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

7
73
0

Year Published

1999
1999
2008
2008

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 69 publications
(80 citation statements)
references
References 48 publications
7
73
0
Order By: Relevance
“…Moreover, as recently shown for the KIR molecules (67), the N-terminal and C-terminal ITIMs may have different efficiencies to associate with phosphatases in vivo, because the N-terminal ITIM was found to be sufficient to recruit SHP-2 but not SHP-1, while both ITIMs were required to recruit SHP-1. In keeping with this, the recently described T cell transmembrane adaptor protein SIT, which contains only one I/VxYxxV ITIM among its four cytoplasmic YxxL/V tyrosine motifs, associates in vivo with SHP-2, but not with SHP-1 and SHIP (68). Thus, this suggests that the presence of a threonine (T) instead of a hydrophobic residue at position Ϫ2 of the C-terminal tyrosine-based motif of FDF03 (TLYSVL), may decrease its potential association with SHP-1 but not with SHP-2, as seen in our study.…”
Section: Discussionmentioning
confidence: 97%
“…Moreover, as recently shown for the KIR molecules (67), the N-terminal and C-terminal ITIMs may have different efficiencies to associate with phosphatases in vivo, because the N-terminal ITIM was found to be sufficient to recruit SHP-2 but not SHP-1, while both ITIMs were required to recruit SHP-1. In keeping with this, the recently described T cell transmembrane adaptor protein SIT, which contains only one I/VxYxxV ITIM among its four cytoplasmic YxxL/V tyrosine motifs, associates in vivo with SHP-2, but not with SHP-1 and SHIP (68). Thus, this suggests that the presence of a threonine (T) instead of a hydrophobic residue at position Ϫ2 of the C-terminal tyrosine-based motif of FDF03 (TLYSVL), may decrease its potential association with SHP-1 but not with SHP-2, as seen in our study.…”
Section: Discussionmentioning
confidence: 97%
“…SIT has been reported to act as a modulator of TCR-mediated signaling (29,35). Indeed, when overexpressed in Jurkat T cells, wild-type (wt) SIT exerts strong negative regulatory effects upon TCR-mediated activation of the transcription factor NF-AT (29,35) This inhibitory effect seems to be exclusively mediated via a single TBSM within the SIT cytoplasmic domain (YASV) that binds a still-to-be-defined ligand. In contrast, overexpression of a SIT mutant lacking the YASV motif strongly amplifies TCR signals.…”
mentioning
confidence: 99%
“…As this regulatory system appears to be crucial for cell fate specifications in the thymus, it is not surprising that the molecules controlling the process are physically located at the plasma membrane as a part of, or in close proximity to, the receptor. In fact, we have shown that TRIM is an integral component of the TCR/CD3 complex (8,45), whereas SIT was identified as a protein co-immunoprecipitating with CD3 (9). Surprisingly, such an elaborated system for fine-tuning TCRmediated signals does not seem to play a role during peripheral T cell activation, as mutations in the number of TCR-ITAMs (41,42) or loss of SIT and TRIM (data not shown) only minimally affect activation of mature T cells.…”
Section: Discussionmentioning
confidence: 98%
“…SIT and TRIM are structurally strongly related proteins. Indeed, they both are non-raft-associated homodimeric transmembrane adaptors and both possess several tyrosine-based signaling motifs (TBSMs) within their cytoplasmic domains, two of which are highly conserved between the two molecules (YGNL and YASV in SIT, and YGNL and YASL in TRIM) (8,9). Interestingly, we have previously reported that the ability of SIT to modulate TCR-mediated signaling in the Jurkat T cell line is determined by these two TBSMs (10).…”
mentioning
confidence: 99%